The genetic heterogeneity and drug resistance mechanisms of relapsed refractory multiple myeloma - Josh N. Vo; Yi-Mi Wu; Jeanmarie Mishler; Sarah Hall; Rahul Mannan; Lisha Wang; Yu Ning; Jin Zhou; Alexander C. Hopkins; James C. Estill; Wallace K. B. Chan; Jennifer Yesil; et al. (Nature Communications, 2022)
The genetic factors involved in disease progression and drug resistance in multiple myeloma (MM) are varied and complex. Here, genomic and transcriptomic profiling of 511 relapsed and refractory MM patients reveals genetic alterations in several oncogenic pathways contributing to progression and resistance to MM therapies.